Penggunaan Media Audio Visual untuk Memotivasi Belajar Siswa Kelas III MI Miftahul Ulum Surabaya - Noviardani Kartika Prameswari; Ajeng Fitri Amalia; Norma Diana Fitri; Alfina Citrasukmawati (Medan Resource Center, 2023)
This descriptive qualitative study investigates the utilization and challenges associated with audio-visual media in enhancing the motivation of third-grade students at MI Miftahul Ulum Surabaya. Data collection involved observations, interviews, questionnaires, and documentation. Findings demonstrate that the use of audio-visual media effectively captures students' attention, increasing their motivation to actively engage in learning and facilitating comprehension of instructional content. However, challenges arise from limited access to necessary tools and the time-consuming preparation process for audio-visual materials. Thus, careful and thorough preparation is essential to ensure the optimal use of audio-visual media, enabling more effective learning experiences for students. Addressing these constraints can contribute to the successful integration of audio-visual resources in educational settings.